Proceedings of DiSS 2019 2019
DOI: 10.21862/diss-09-019-bakti
|View full text |Cite
|
Sign up to set email alerts
|

Error type disfluencies in consecutively interpreted and spontaneous Hungarian speech

Abstract: Interpreting can be considered as a form of spontaneous speech, the key differences being that language change is involved in interpreting and the fact that speech production is influenced by several constraints during interpreting. Research has shown that the interpreting task influences the disfluency patterns of target language texts. The aim of this paper is to investigate how the frequency and distribution of error type disfluencies changes in the target language output of trainee interpreters as they pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…To map the development of consecutive interpreting skills, a longitudinal study was conducted at the University of Szeged. In the consecutively interpreted Hungarian target language output of interpreter trainees, the frequency of occurrence of speech errors (error-type disfluencies [ETDs], like grammar errors, blends, false word errors) [9] were examined. Results showed that the average frequency of speech errors does not change considerably as students progress in their interpreter training, however, considerable individual differences exist.…”
Section: Introductionmentioning
confidence: 99%
“…To map the development of consecutive interpreting skills, a longitudinal study was conducted at the University of Szeged. In the consecutively interpreted Hungarian target language output of interpreter trainees, the frequency of occurrence of speech errors (error-type disfluencies [ETDs], like grammar errors, blends, false word errors) [9] were examined. Results showed that the average frequency of speech errors does not change considerably as students progress in their interpreter training, however, considerable individual differences exist.…”
Section: Introductionmentioning
confidence: 99%